(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
ينشد هذا البحث بيان الصلة بين الشاعر القديم والطبيعة ممثلة بالروضة، والوقوف على أساليب الشعراء القدامى في توظيف الروضة الشعرية، في التعبير عن مكنونات النفس، وصوغ صور جزئية، وكلّيّة مشحونة بالمشاعر والانفعالات، ومنطوية على رموز غنيّة، ودلالات خفيّة موصولة بالمرأة. وفي سبيل ذلك، يدرس البحث ثلاثة نصوص شعرية، تتسم ببراعة أصحابها ومهارتهم في المزج الفنيّ المحكم بين الروضة والمرأة – المحبوبة. وقد اقتطعت من ثلاث قصائد لثلاثة شعراء قدماء، هم: عنترة بن شدّاد العبسيّ، والأعشى الكبير، والنَّمِر بن تَوْلَب. والدراسة نصّيّة تحليلية، لا تقيّد نفسها بمنهج محدد، وإنما تستنير بإضاءات من مناهج الدرس الأدبي، رغبة من الباحث في تفسير النصوص تفسيراً دقيقاً، وتأويل المعاني فيها تأويلاً سليماً، وأملاً في بلوغ صورة للبحث دانية من التكامل؛ علّه بذلك يلتمس لنفسه حيّزاً ملائماً في حقل الدراسات التراثية؛ الأدبية، والنقدية. This research aims at exposing the relation between the Old Poets and nature represented by the Oasis. It examines these poets’ techniques and methods in exploiting the poetic oasis to express their inner feelings and emotions and to create imagery which, in its partiality and entirety, is filled with emotions and embodies very rich symbolism and hidden meanings related to the woman. The research examines three texts characterized by the mastery of the poets who composed them and their brilliance in achieving a perfect artistic combination between the oasis and the woman-beloved. The texts are taken from three poems by three Old Poets, Antara Bin Shaddad Al-Absi, Al-A’sha Al-Kabeer, and Al-Namir Bin Tawlab. This study is basically a textual analysis, which does not restrict itself to a specific critical approach. It employs different literary approaches due to the researcher’s aim to produce an accurate interpretation, as well as, a sound reading of the texts, hoping to introduce the research in the best possible form which may entitle it to occupy a suitable place in the field of cultural studies, both literary and critical.